Discussion on the contribution of behavioral psychology and neuroscience in Law - Bullard González, Alfredo (2014)
The current round table gathers four renowned specialists infields such as Law and Economics, Civil Law, Litigation, and others, inorder to discuss the relevance and impact of the development of behavioral psychology and neuroscience in Law. thus, the guests addressthe criticism directed from the mentioned study fields to the modelof individual rationality that underlies traditional legal institutions.